Examine Living Space on the Human Settlement Around the Market:The Problems of the City on the Macro and Micro Scale - Suganda, Emirhadi; Atmodiwirjo, Paramita; Yatmo, Yandi Andri (UI Scholars Hub, 2009)
There have been some misfits between the practice of urban planning at a macro scale and the needs of the society at a micro scale. This paper intends to discuss this issue by illustrating a case of high density urban housing as a supporting system for the activities in a traditional market as urban public facilities. The case suggests a dialog between the physical space determined by macro-scale planning and the everyday social life of the community living in the housing surrounding the market. The housing plays an important role as a living space for the market workers and as a setting for various activities that support the trading activities in the market. Unfortunately, there is a tendency that despite its importance, the quality of the housing is still far from sufficient as a space for living. The findings in this study suggest that the practice of urban design, especially in the provision of public facilities, needs to integrate macro urban scale with more micro everyday life of the communities. The practice of urban design needs to be sensitive to the diversity in urban environment and the interrelationships between urban elements. In this way, it would be possible to create urban environment that caters for the needs of its inhabitants in a sustainable way, both at macro scale and micro scale.